Pengelolaan, Proses, dan Dampak Sudut Buku bagi Siswa Pendidikan Dasar - Agnes Prabaningrum; Suyono Suyono; Titik Harsiati (Graduate School of Universitas Negeri Malang, 2021)
Abstract: The book corner of the classroom can support the School Literacy Movement at the basic education level. So, this research sees its management, the process of its use, and its impact. This study used a literature review design with meta theory methods. Data in the form of verbal exposure. Sources of data from reputable national and international journals. The technique of reading data is critical reading. Data analysis was carried out through the next stages of preparation, analysis, and conclusion. The results showed that the management was carried out in three ways by designing, enriching the collection of books according to the character of the students, and arranging and then determining the visiting regulations. Book corners can be used at recess, in the middle of the learning process, even after school. Book corners can be used for individual or group literacy activities. The positive impacts for students are (1) growing interest in reading, making students like reading, increasing literacy skills, increasing achievement, hone creativity, fostering an attitude of responsibility and teaching students to be tolerant. Meanwhile, the positive impacts for teachers are (1) application of Gerakan Literasi Sekolah and (2) assist in learning activities.Abstrak: Sudut buku kelas dapat menunjang Gerakan Literasi Sekolah di tingkat pendidikan dasar. Maka, penelitian ini dilakukan untuk mengetahui penglolaannya, proses pemanfaatannya, dan dampaknya. Penelitian ini menggunakan desain kajian pustaka metode metateori. Data berupa paparan verbal. Sumber data dari jurnal nasional dan internasional bereputasi. Teknik pengumpulan data adalah membaca kritis. Selanjutnya analisis data dilakukan melalui tahap persiapan, penganalisaan, dan penyimpulan akhir. Hasil penelitian menunjukkan bahwa pengelolaan dilakukan dengan tiga cara yaitu mendesain, memperkaya koleksi buku sesuai karakter siswa, dan melakukan penataan lalu menetapkan peraturan kunjungan. Sudut buku dapat dimanfaatkan pada waktu istirahat, di tengah proses pembelajaran, bahkan setelah pulang sekolah. Sudut buku dapat dimanfaatkan untuk kegiatan literasi secara individu maupun kelompok. Dampak positif bagi siswa yaitu (1) menumbuhkan minat baca, membuat siswa menjadi gemar membaca, meningkatkan kemampuan literasi, meningkatkan prestasi, mengasah kreativitas, memupuk sikap tanggungjawab dan mengajari siswa untuk toleransi, sedangkan dampak positif bagi guru yaitu (1) mempermudah penerapan Gerakan Literasi Sekolah; (2) membantu dalam kegiatan pembelajaran.